Association between personality traits and concerns about falling among older patients: the mediating role of subjective age - Rongrong Fan; Lili Wang; Wenxiu Wang; Yanan Zhong; Tingting Zhang; Xia Yang; Jing Zhu (Frontiers Media S.A., 2024)
BackgroundOlder patients are at high risk of falling, and regular assessments of their concerns about falling (CaF) are often recommended. The present study aimed to investigate the association between CaF and personality traits among older patients as well as to elucidate the mediating role of subjective age.MethodA cross-sectional study was conducted among 407 patients aged over 60 years in a tertiary hospital located in Chengdu, Sichuan Province, from March 2023 to May 2023. Predesigned electronic questionnaires were distributed to collect relevant data. Four different models (both crude and adjusted weighted linear regression models) were constructed based on the confounders. Confounders were gradually put into the models to control for bias and to examine the stability of the correlations. Bootstrap sampling was employed to examine the mediating role of subjective age.ResultAccording to the fully adjusted model, neuroticism (β = 0.17, 95% CI: 0.02 to 0.31, p for trend = 0.02), extraversion (β = −0.07, 95% CI: −0.15 to 0.001, p for trend = 0.05), and subjective age (β = 2.02, 95% CI: 1.28 to 2.78, p for trend <0.001) were consistently correlated with CaF. Mediating analysis revealed that extraversion was negatively related with CaF both directly and indirectly, via subjective age [23.2% partial effect, bootstrap 95%CI: −0.024(−0.080, −0.000)]. Higher neuroticism was consistently related to older subjective age (β = 0.002, 95% CI: 0.001 to 0.004, p for trend = 0.006), while higher levels of conscientiousness, openness, and extraversion were consistently correlated with younger subjective age(β = −0.002, p for trend = 0.04; β = −0.003, p for trend = 0.003; β = −0.002, p for trend = 0.0, respectively).ConclusionExtraversion and neuroticism were significantly correlated with CaF. Moreover, subjective age partially mediated the relationship between extraversion and CaF. Furthermore, subjective age was found to be associated with both CaF and personality traits. These findings highlighted the important roles of personality traits and subjective age in assessments of CaF and in the development of strategies for preventing falls among older patients.